2018
DOI: 10.2320/matertrans.maw201808
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of Carbon Fiber and Hybrid Carbon Fiber-Carbon Nanofiber Reinforced Aluminum Matrix Composites by Low Pressure Infiltration Process and Their Properties

Abstract: Carbon fiber reinforced pure Al, A336 alloy and carbon fiber-carbon nanofiber reinforced A336 alloy composites were successfully fabricated by low-pressure infiltration process, aiming for development the carbon fiber reinforced aluminum matrix composites with high thermal conductivity and mechanical property used as functional materials and structural materials, respectively. Carbon fiber of 10 vol% and hybrid carbon fiber-carbon nanofiber of 10 vol% were used to fabricated preforms for the low-pressure infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The addition of ZA27 plays a role in the second phase strengthening. The increase in the hardness value of the composite material is also affected by the slightly increased carbide in these materials [28].…”
Section: Hardness Of Composite Materialsmentioning
confidence: 99%
“…The addition of ZA27 plays a role in the second phase strengthening. The increase in the hardness value of the composite material is also affected by the slightly increased carbide in these materials [28].…”
Section: Hardness Of Composite Materialsmentioning
confidence: 99%
“…Carbon fiber reinforced aluminum matrix composites have light weight, high thermal and electrical conductivity, good high-temperature stability, high specific strength, high elastic modulus, and high wear resistance [14,15], and can be widely used as materials and structural materials in the automotive industry. For example, Meng [16] used low-pressure permeation method to prepare carbon fiber reinforced pure aluminum, A336 alloy composites and carbon fiber-carbon nanofiber reinforced A336 alloy composites, and the results showed that the mechanical properties of carbon fiber-reinforced aluminum matrix composites were improved, and the high hardness provided theoretical support for the application of the composites in automobile body and other parts.…”
Section: Introductionmentioning
confidence: 99%
“…CF- reinforced aluminum composites combine the properties of CF and Al, exhibiting low density and excellent mechanical and thermal/electrical properties 2 , and are expected to be utilized as heat sink materials. The conventional infiltration processes for fabricating SCF reinforced Al matrix composites generally use inorganic binders such as SiO 2 3 , Al 2 O 3 4 , or TiO 2 5 for the SCF preform manufacturing. However, preform manufacturing with an inorganic binder is complicated, and the preform needs high temperatures and more time for binder sintering.…”
Section: Introductionmentioning
confidence: 99%